THE INFLUENCE OF APPLICATION OF MODERNIZATION IN TAXATION ADMINISTRATION SYSTEM TOWARD THE LEVEL OF TAX PAYER COMPLIANCE (Study of KPP Pratama Bantul Individual Tax Payers) - Aji Fauzie; Dewi Kusuma Wardani (Jurnal Akuntansi, 2014)
This study aimed to analyze the effect of the implementation of the modernization of the tax administration system of the level of compliance of individual taxpayers in the Tax OfficeBantul Yogyakarta. This study uses judgment sampling and survey method with a questionnaire to collect data. Respondents were sampled in this study is the individual taxpayer listed on the Tax Office Bantul Yogyakarta . Analysis of research data using simple regression with SPSS 16.0 Based on the analysis of the individual results of hypothesis testing shows that the t value for the modernization of the tax administration system variable (X) on tax compliance ( Y ) of 6.329 , mean t count > t table ( 6.329 > 1.991 ) , had a significance level of 0.000 for the level significance smaller than 0.05 , it means that this study shows the modernization of the tax administration system variables significant positive effect on tax compliance Keywords : Modernization of the system of tax administration , tax compliance, tax administration